Faktor-Faktor yang Mempengaruhi Kinerja Pegawai pada Dinas Sosial di Kabupaten Tapanuli Tengah - Nursahara Panggabean (LITERATUS, 2021)
In this study, the limitation of the concepts or research variables used is limited. The employee performance of Social Services in Central Tapanuli Regency in this study is accommodated into components or dimensions that affect employee performance, namely work motivation, leadership, organizational culture, competence and compensation. This study aims to determine which dimensions of the dominant motivational variables affect employee performance of Social Services in Central Tapanuli Regency. The design of this research is a descriptive-explorative approach to examine the dominant factors affecting on employee performance of Social Services in Central Tapanuli Regency. The data analysis technique uses factor analysis. The validity test uses the Corelation Product Moment formula while the reliability test uses the Cronbach method (Alpha/Reablity Analysis). There are 3 (three) dominant factors that influence employee performance of the Social Service in Central Tapanuli Regency. The main dominant factors in the competency dimension are skills and knowledge (46.47%). The manivest variable of the compensation dimension, after being reduced / extracted, also forms 3 (three) components / dominant factors, on the weight of the factor of the compensation dimension, allowance has the greatest weight, namely 24.47.%. In the dimension of work motivation factor, it is known that the factor that gives a big or dominant contribution to the improvement on employee performance of Social Services in Central Tapanuli Regency is the need for achievement (49.30%). employees of the Social Services in Central Tapanuli Regency are the implementation of leadership functions (50.47%).